The Construction Method of NC Lathe Programming and Machining Micro Course Resources - Qi, Xiaoguang; Yuan, Yuan; Ren, Tingting (Journal of Theory and Practice of Social Science, 2023)
With the continuous development of social economy and science and technology, China's various industries have increased the demand for talents, the increase of social demand for talents has promoted the development of higher vocational colleges, making the scale of Higher Vocational Colleges continue to expand in the current social development of our country. In the development of China's colleges and universities, no matter at any stage, attach importance to the education of students' cultural theory courses, but not too much education of Ideological Courses, which leads to students' lack of their own political and ideological ideas, and there are some conflicts in Ideological and political learning. English is an important course in the study of higher vocational colleges. In order to effectively enhance the ideological and political education in Colleges and universities, ideological and political education can be run through English teaching to cultivate students' comprehensive quality development. This paper mainly analyzes and studies the construction of Ideological and political education system in Higher Vocational English teaching. At present, there are two major problems in the use of video resources in the process of video recording and video analysis. On the other hand, there are two major problems in the use of video resources in the process of video teaching Methods, shooting video, making video, post editing and so on, and the implementation of recording screen is mainly carried out by recording screen software. Another kind of real-time video needs to shoot the content first, and then use professional video editing software for post production and processing, such as PR, love editing and other software.